Hospital Services Quality from Patients' viewpoint in Iran: A Systematic Review and Meta-Analysis - Mohammad Mohseni; Ahmadreza Raeisi; Saber Azami-Aghdash; Ahmad Moosavi; Seyed Masood Mousavi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The identification of strengths and weaknesses of services provided is the first step for the improvement of the quality of services. In hospitals, patients are the most important groups for the evaluation of the quality of healthcare services. Thus, this systematic review and meta-analysis aims to evaluate hospital service quality from patients’ perspective in Iran using Servqual model. Methods: A systematic review and meta-analysis of studies evaluating patients’ perspective about hospital services quality was conducted. Required data were collected through searching following key words: Servqual, services quality, gap, hospital, patients, Iran, using the database sources including PubMed, Scopus, Google Scholar, MagIran, SID and IranMedex. Comprehensive meta-analysis (CMA) software, Version 2 was used to estimate the total mean score of patients’ perception and expectation of services quality and the gap between them. Results: Totally, 11 eligible studies were entered into the systematic review. Based on the random effect model, the total mean score of patients’ perception, patients’ expectation and the gap between them were estimated 3.66 (95% CI, lowest = 3.40, highest = 3.92), 4.62 (95% CI, lowest = 4.42, highest = 4.82) and 0.94 (95% CI, lowest = 0.78, highest = 1.10), respectively. The mean score of the gap between perception and expectation was 0.95 and the biggest gap was related to the responsiveness dimension. Conclusion: Responsiveness is related to the areas, such as providing appropriate and timely services, the reliability of providers, good communication between staff or physicians and patients. The importance of these areas signifies the necessity of taking actions in order to provide more appropriate and higher quality services.